A new species of Calocybe (Agaricales, Basidiomycota) from China - Mu, Lisong; Bau, Tolgor (Phytotaxa, 2023)
Morphological and molecular phylogenetic data were used to describe a new Calocybe species (C. violacea) collected from Yunnan Province, China. Calocybe violacea is characterized by its convex to applanate, purple to bluish-purple pileus; purple-black, bluish-purple to white stipe; and relatively larger basidiospores. Phylogenetic analyses of the combined ITS and nrLSU loci supported the distinct position of this proposed new species, showing that C. violacea clustered in a single sister clade with C. vinacea.